Board interlocks’ reported benefits and drawbacks : A sustainability perspective - Codina, Rosa (2021)
Current global sustainability concerns call for urgent solutions through the collective effort of government and organizational actors, since they are at the front of sustainable policy and strategy development. Within a corporate context, board interlocks may represent an innovative way to overcome some of the traditional constraints associated with the incorporation of sustainability practices within firms. Nevertheless, the efficiency of these efforts depends on the sustainability objectives set out by firms. This paper argues that interlocking directorates can be a valuable governance mechanism for disseminating and implementing sustainability practices within organizations as well as for achieving strategic sustainable development goals. However, this capacity is limited by the size and diversity of board members, as well as by the sectors in which interlocked directors operate.